Five Trends in Supply Chain Management that can make SMEs and F-Commerce more competitive: A perspective of fashion tunnel - Ahmed, Fabiha Farzin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2022.